Detection of Animal Fat Mixtures in Meatballs Using Fourier Transform Infrared Spectroscopy (FTIR Spectroscopy) - Fajriati, Imelda; Rosadi, Yusi; Rosadi, Nisrina Nabila; Khamidinal, Khamidinal (Indonesian Journal of Halal Research, 2021)
Detection of animal mixtures in meatballs by using Fourier Transform Infrared Spectroscopy (FTIR spectroscopy) has been studied. This research aims to study the different markers of fat characters in meatballs containing the mixture of chicken fat, lard and rat fat. Sample preparation used Soxhlet extraction with n-hexane solvent and distillation of fat from the solvent. The extraction temperature is 70Â°C with solvent volume 200 mL. Fat samples were prepared by varying the ratio of 100% chicken fat concentration which corresponds to 1%, 10%, and 20% lard, and 1%, 10%, and 20% rat fat. The meatballs were made with a composition of 0%, 5% and 90% rat meat. The result of FTIR interpretation shows that the increasing concentration of the mixture of lard and rat fat have increased the absorption at wave numbers of 3371 cm-1, 3332 cm-1, 2337 cm-1, and 1743 cm-1. The FTIR spectrum is interpreted based on the uptake of typical functional groups of animal fats. The characteristics of animal fat properties can be distinguished by consistent results using infrared spectroscopy.